A computed tomographic graphical approach to guide correction of femoral torsion. Issue 5 (9th May 2020) - Eby, Adam; Bleedorn, Jason
Abstract: Objective: To report geometric methods to assess femoral transverse bone morphology and develop a virtual method to guide the surgical correction of femoral torsional deformities. Study design: Observational study. Sample population: Sixteen client‐owned dogs comprising 14 normal femurs and 14 femurs with angulation‐rotation bone deformities. Methods: Femoral torsion angle was measured with computed tomographic (CT) three‐dimensional (3D) multiplanar reconstruction. Distal femoral transverse morphology was estimated with geometric methods and compared to direct measurements to span a target 20° angle on 3D reconstructions. A virtual correction of 20° was performed, and 3D‐printed bone models were created. Femoral torsion of corrected bone models was compared to precorrection. Results: Geometric estimates with an arc and chord of the metaphyseal area and chord of a best fit circle did not differ from direct measurement of femoral cortical length along the cranial cortex. Femoral torsion differed between normal femurs (25.8° ± 6°) and those with deformity (36.9° ± 8.4°, P < .001). Torsion that was measured on corrected 3D bone models did not differ from the expected torsion (preoperative +20°). Conclusion: Geometric methods provided an accurate estimate of distal femoral transverse bone morphology. Rotation of the distal femur based on geometric methods resulted in an accurate correction of torsion. Clinical significance: Femoral bone diameter can be measured on a CT cross‐section, and rotation distance can be calculated to achieve a desired correction of torsion. This approach provides a simple and accurate method to guide the correction of femoral torsion.